A Carbon‐ and Binder‐Free Nanostructured Cathode for High‐Performance Nonaqueous Li‐O2 Battery. Issue 8 (18th June 2015) - Chang, Yueqi; Dong, Shanmu; Ju, Yuhang; Xiao, Dongdong; Zhou, Xinhong; Zhang, Lixue; Chen, Xiao; Shang, Chaoqun; Gu, Lin; Peng, Zhangquan; Cui, Guanglei
<x xml:space="preserve">Abstract</x> Operation of the nonaqueous Li–O2 battery critically relies on the reversible oxygen reduction/evolution reactions in the porous cathode. Carbon and polymeric binder, widely used for the construction of Li–O2 cathode, have recently been shown to decompose in the O2 environment and thus cannot sustain the desired battery reactions. Identifying stable cathode materials is thus a major current challenge that has motivated extensive search for noncarbonaceous alternatives. Here, RuOx/titanium nitride nanotube arrays (RuOx/TiN NTA) containing neither carbon nor binder are used as the cathode for nonaqueous Li–O2 batteries. The free standing TiN NTA electrode is more stable than carbon electrode, and possesses enhanced electronic conductivity compared to TiN nanoparticle bound with polytetrafluoroethylene due to a direct contact between TiN and Ti mesh substrate. RuOx is electrodeposited into TiN NTA to form a coaxial nanostructure, which can further promote the oxygen evolution reaction. This optimized monolithic electrode can avoid the side reaction arising from carbon material, which exhibits low overpotential and excellent cycle stability over 300 cycles. These results presented here demonstrate a highly effective carbon‐free cathode and further imply that the structure designing of cathode plays a critical role for improving the electrochemical performance of nonaqueous Li–O2 batteries.